Math, asked by arisha614, 10 months ago

kindly solve this question step by step & I will mark as brainlist

Attachments:

Answers

Answered by anindyaadhikari13
4

Here is the full solution:-

 (\frac{ - 1}{2})^{4}  \times  {3}^{3}  \times  {( \frac{2}{3} )}^{4}

 = ( \frac{1}{2} )^{4}  \times  {3}^{3}  \times  \frac{ {2}^{4} }{ {3}^{4} }

 = ( \frac{1}{ \cancel{2^{4} }})  \times  {3}^{3}  \times  \frac{  \cancel{{2}^{4}} }{ {3}^{4} }

 =  {3}^{3 - 4}

 =  {3}^{ - 1}

 =  \frac{1}{3}

Answer:-

  • Answer is  \frac{1}{3}
Answered by Anonymous
0

Answer:

 \frac{1}{16}  \times  27 \times  \frac{16}{81}

 \frac{1}{3}

is correct answer

Similar questions